KUALITAS PELAYANAN RAWAT JALAN PUSKESMAS TANJUNG PALAS BERDASARKAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Imam Muazansyah; Irsyad Sudirman (Department of Public Administration, Universitas Negeri Surabaya, 2019)
This study was to analyze the quality of outpatient services at Tanjung Palas Community Health Center using the Importance Performance Analysis method. Population collection uses non probability sampling through convenience sampling. The questionnaire was distributed to 99 respondents who were samples of outpatients at the Tanjung Palas health center. The outpatient satisfaction index using the Importance Performance Analysis (IPA) obtained the results of research that service quality had a significant impact on patient satisfaction with service users with proven reality or performance of health centers that were far from patient expectations, patients were less satisfied with the services provided by the Center health, especially in attributes or quadrant I, namely cleanliness of the health center, completeness of medical devices, and reliability of health personnel both doctors and nurses.